Aspectos legais que compõem os repasses para financiar o orçamento da educação básica : um estudo de caso do município de Passo Fundo/RS para o exercício de 2011 - Pavan, Rafael (2013)
This thesis conducted a study of the contributions involving the legal tax system, with emphasis on knowledge of the tributes that have a direct link with the maintenance and development of basic education. Taking the case study methodology as a basis, the space of real application of the rules of the tax system chosen was the city of Passo Fundo, located north of the State of Rio Grande do Sul, since the municipality proposes in its Organic Law the annual application of 35% of the resulting tax revenue, understood also from transfers, maintenance and development of basic education council. Thus, we analyzed the relationship between the inputs and the concreteness of legal funding and maintenance of basic education in the county in screen. To achieve the objectives, the methodology used was qualitative and quantitative, anchored in the following: identifying conceptual, structural and operational budget as revenue and public expenditure to fund the municipal basic education through a literature a descriptive and case study. We conclude that the district under study has been serving the legal regulations, especially with regard to the application of 35% of its tax revenues and current transfers in the Maintenance and Development of Basic Education - MDE. As a contribution, the study also presents important dimensions for the interface between law enforcement and the concreteness of the budget on education, producing summaries significant for future studies and grants for public managers